2019
DOI: 10.1186/s12874-019-0769-x
|View full text |Cite
|
Sign up to set email alerts
|

Ranking hospital performance based on individual indicators: can we increase reliability by creating composite indicators?

Abstract: Background Report cards on the health care system increasingly report provider-specific performance on indicators that measure the quality of health care delivered. A natural reaction to the publishing of hospital-specific performance on a given indicator is to create ‘league tables’ that rank hospitals according to their performance. However, many indicators have been shown to have low to moderate rankability, meaning that they cannot be used to accurately rank hospitals. Our objective was to def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…In general, low rankability is defined as ,50% and no ranking attempt should be made when rankability is low. 11,13 Besides our definition of high rankability as above 75%, 11 it has been suggested that above 70% is fair to rank hospitals, 14 meaning QI 6 was the only fair indicator.…”
Section: Discussionmentioning
confidence: 92%
“…In general, low rankability is defined as ,50% and no ranking attempt should be made when rankability is low. 11,13 Besides our definition of high rankability as above 75%, 11 it has been suggested that above 70% is fair to rank hospitals, 14 meaning QI 6 was the only fair indicator.…”
Section: Discussionmentioning
confidence: 92%
“…The same applies for low figures: our lowest ICC1, 0.068 corresponded with the lowest rankability, 0.144 (for polypharmacy). This relationship has been explored with a similar correlation for the ranking of binary hospital quality indicators [ 20 ]. Although an ICC1 of 0.05 has been regarded as the lower threshold for quality indicators, considering the rankability found in our study, this threshold might be higher, at roughly 0.15.…”
Section: Discussionmentioning
confidence: 99%
“…We also explored quality indicators’ rankability, i.e., the part of variability between nursing homes measured by quality indicators that results from true differences in quality of care [ 35 ]. High rankability for a particular indicator allows performance ranking for that indicator, e.g., polymedication [ 20 ]. Rankability (ρ) is defined as: ρ = VG /( VG + median ( s 2 )), with median ( s 2 ) indicating the variance of the individual facility effect estimates from a fixed effect regression model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome measures are increasingly used to rank institutions inevitably giving the appearance of ranking quality of care [4]. Rankability measures the proportion of the variation between providers with regards to an outcome that is due to true differences; it is considered high if above 70% [34]. No study in this review directly assessed the rankability of LOS as an outcome measure in CAP.…”
Section: Discussionmentioning
confidence: 99%